Timor Collision Front Segmentation Reveals Potential for Great Earthquakes in the Western Outer Banda Arc, Eastern Indonesia - Coudurier-Curveur, Aurélie; Singh, Satish C.; Deighton, Ian (Frontiers in Earth Science, 2021)
In Eastern Indonesia, the western Outer Banda arc accommodates a part of the oblique Australian margin collision with Eurasia along the Timor Trough. Yet, unlike the Wetar and Alor thrusts of the Inner Banda arc in the north and the adjacent Java subduction zone in the west, both recent and historical seismicity along the Timor Trough are extremely low. This long-term seismic quiescence questions whether the Banda Arc collision front along the Timor Trough is actually fully locked or simply aseismic and raises major concerns on the possible occurrence of large magnitude and tsunamigenic earthquakes in this vulnerable and densely populated region. Here, we jointly analyze multibeam bathymetry and 2D seismic reflection data acquired along the Timor Trough to characterize the location, nature, and geometry of active faults. Discontinuous narrow folds forming a young accretionary prism at the base of the Timor wedge and spatially correlated outcropping normal faults on the bending northwest Australian shelf reveal two concurrent contrasting styles of deformation: underthrusting and frontal accretion. We find that those tectonic regimes and their associated seismic behaviors depend on 1) the thickness of the incoming and underthrusting Cenozoic sedimentary sequence, 2) the vergence of inherited normal faults developed within the continental shelf, and 3) the depth of the décollement beneath the Timor wedge. Based on the along-strike, interchanging distinct deformation style, we identify the mechanical and seismic segmentation along the Banda arc collision front and discuss the implications for earthquake and tsunami hazards along the western Outer Banda arc region.